Staging the intimate-public camera: Wen Hui's documentary practice with her third grandmother. Issue 1 (2nd January 2020) - Zhang, Zhen
ABSTRACT: This article highlights pioneering dancer, choreographer, and multi-media artist Wen Hui's unique contribution to Chinese independent cinema and first person documentary by analyzing her two films made with her 'forgotten' third grandmother. The close reading is grounded in her explorations in intermedia performance and documentary theater centered on body as archive of memory and women's experience. I argue that Listening to Third Grandmother and Dancing with the Third Grandma experiment with an intimate-public camera for constructing a female kinship outside the patriarchal family tree and re-writing women's history through oral storytelling and choreography of the everyday.